PENGARUH NILAI OKTAN DAN KONDUKTIVITAS BUSI TERHADAP TORSI SEPEDA MOTOR 115 cm3 : EFFECT OF OCTANE VALUE AND SPARK PLUG CONDUCTIVITY ON MOTORCYCLE TORQUE 115 cm3 - Wisnu Haryoko (Jurnal Teknik Mesin, 2024)
The purpose of this study was to determine the effect and interaction of treatment of octane value and spark plug conductivity on motor 115. The octane used is RON 90, RON 92, and RON 98 and the spark plugs used are Copper, Platinum and Iridium spark plug conductivity with Copper Thermal Conductivity 401 W/m.K, Platinum 71.6 W/m.K, Iridium reaches 147 W/m.K. The method of this research was carried out using experimental methods in a dynamometer engine to determine the results of torque by testing at several rpm. The results of this study indicate that the octane value and spark plug conductivity have a significant effect while the treatment interaction between the octane value and spark plug conductivity does not have a significant effect on the torque of the 115 cm3 motor. The highest torque occurred at 4500 rpm with the use of RON 92 and conductivity of Copper and Iridium spark plugs, with an average torque value of 8.41 N.m. followed by conductivity of Copper spark plugs having a torque value of 8.40 N.m.. Meanwhile, the lowest torque value occurs at 7000 rpm with the use of RON 98 and conductivity of platinum spark plugs, with an average torque value of 5.74 N.m. followed by conductivity of Copper spark plugs with an average torque value of 6.07 N.m. and conductivity of Iridium spark plugs which have a torque value of 6.12 N.m.